POTENSI FILTRAT UMBI TALAS (Colocasia esculenta (L.) Schott) SEBAGAI ANTIKOAGULAN - Shabrina Dewi Ramadhani; Muhammad Arsyad; Nafila Nafila; Dian Nurmansyah; Maya Herliana Sasmitha (Klinikal Sains : Jurnal Analis Kesehatan, 2023)
A Clinical laboratory is a health laboratory that carries out clinical specimen examination services with the type of blood test material. Blood that is used as an examination material sometimes requires additional substances that can inhibit blood clotting such as anticoagulants. Natural ingredients that are thought to have anticoagulant content are taro tuber filtrate (Colocasia esculenta (L.) Schott). This study aimed to determine the potential of taro tuber filtrate (Colocasia esculenta (L.) Schott) as an alternative anticoagulant. The method used in testing anticoagulant activity is Clotting Time in Vitro. Taro tubers are grated and filtered to obtain filtrate from taro tubers. Taro tuber filtrate test samples are divided into 5 concentrations of 10%, 30%, 50%, 70%, and 90%. Each concentration was carried out 4 times with each treatment given a blood sample of 1 mL. The results of the phytochemical screening test of taro tuber filtrate contain secondary metabolite compounds of flavonoids, alkaloids, and saponins that have anticoagulant activity. Based on the results of clotting time testing that 1 mL of blood mixed with 10% taro tuber filtrate clotted after the 15th hour, while concentrations of 30%, 50%, 70%, and 90% did not occur blood clots after observation for 6 days. Based on the results of research that has been done, it can be concluded that taro tuber filtrate (Colocasia esculenta (L.) Schott) has the potential as an alternative anticoagulant